STRATEGI PENGEMBANGAN DESA WISATA GELGEL BERBASIS BUDAYA DI KABUPATEN KLUNGKUNG - Putra, I Kadek Wira Adi; Vipriyanti, Nyoman Utari; Agung, Anak Agung Putu; Sanjaya, I Putu Agus (Jurnal Alam Lestari, 2021)
Gelgel Village is a village in the Klungkung subdistrict area which was designated as a tourism village in 2017, which is known as the biggest and winning royal story in Bali, namely the Kingdom of Gelgel. The potential of history, culture, economy, natural resources and human resources is not optimal as a tourism village potential. A tourism management system that is not yet synergistic between the relevant stakeholders. This research discusses the development of tourism potential, analyzes internal and external environmental conditions and formulates strategies to develop Gelgel village. The method of data collection is done through interviews, questionnaires, focus group discussions and documentation. The analytical method consists of qualitative descriptive, weighting and evaluation with SWOT and AHP (Analytical Hierarchy Process) analysis. The potential of the Gelgel village include a historical building in the kingdom of Gelgel, the shrine of Dasar Bhuana Gelgel, the tourist attraction of craft weaving and the natural attraction of beach Batu Tumpeng. The results of the evaluation of internal and external factors (IFE-EFE) showed that the score of internal factors was 3.07, while the score of external factors was 3.10. The priority strategy based on the results of the SWOT and AHP analysis is an average score of 0.137 or 13.7% that is to manage the environment and infrastructure in the tourist area of Gelgel village.